An IoT architecture for smart rice monitoring - Charoenporn, Pattama (My University, 2019)
This paper presents an architectural design process for the IoT rice system which derives approach from the finding model. This model design from three-tier architecture, agile methodology and IoT architecture model. We receive input data from interview 400 farmers who crop rice live in the north-east of Thailand. Then we compare 10 models from 5 pieces of literature to design a conceptual model. The conceptual model present 2 models, it composes of web service design from service-oriented architecture and the other model present web application design from HTTP, JavaScript. The results show that web service is the best way to implement IoT rice system because the concept of service-oriented architecture is supported the relationship between communication protocol over the network. After that, we create a conceptual model, that follows from 400 farmers to present to those who want to implement the real application.
Keywords: Architecture design; Conceptual modeling; IoT architecture; Process Model